Differential analysis of fish meal substitution with two soybean meals on juvenile pearl gentian grouper - Pang, Aobo; Xin, Yu; Xie, Ruitao; Wang, Zhuoduo; Zhang, Wei; Tan, Beiping (Frontiers in Marine Science, 2023)
Fermented soybean meal (FSBM) and soybean protein concentrate (SPC) are products of soybean that have been processed physically or biologically, and their use as an alternative to fish meal (FM) results in a significant reduction in the effects of anti-nutritional factors (ANFs) in soybean on aquatic species. Replacing FM with SPC and FSBM can meet the high protein requirements of carnivorous fish while effectively reducing aquaculture costs; however, excessive substitution can also cause economic losses. In this study, we used transcriptome sequencing to investigate the impacts of FSBM and SPC on the growth and physiology of pearl gentian grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) juveniles and to examine the mechanisms by which SPC and FSBM impair the intestinal condition of fish. Originally weighed 12.55 ± 0.06 g, the selected pearl gentian groupers were categorised into three treatment groups: one group was fed FM-based diets (FM, control group), one group was fed FM- and SPC-based diets (SPC40) and one group was fed FM- and FSBM-based diets (FSBM40), with the same crude protein and crude fat content in all three diets. The experiment was conducted for 10 weeks. The growth results showed that both the SPC and FSBM diets significantly inhibited the growth of the fish. Based on the results of enzyme activity, substance content and gene expression levels associated with intestinal damage and intestinal inflammation, it is highly likely that the SPC and FSBM diets affected the intestinal health of the fish and triggered intestinal inflammation. This study provides a theoretical basis to further explore the mechanism of soybean-initiated intestinal problems in fish.